Bioaccumulation Of Heavy Metal Mercury (Hg) In Rain Season In Culture Of Green Mussel (Perna viridis) On Cirebon Water, West Java - Dewi Nurhayati; Didha Andini Putri (Journal of Aquaculture Science, 2018)
A Study was conducted to determine the bioaccumulation of heavy metal mercury (Hg) by the tissue of Perna viridis (green mussel), water, and sediment collected from culture of green mussel in Cirebon water, West Java on rainy season February 2018. Sediments, green shells of P. viridis, and water were taken from the culture of green mussel of Cirebon waters. Samples were taken during the rainy season in February at harvest age ie 6 months of maintenance. Seawater, sediment, and green shell samples were taken 3 replications. Testing of mercury (Hg) heavy metals follows SNI 01-2354.6-2006 measured in the laboratory of Research and Development Guidance of Quality of Fishery Products (BPPMHP) Cirebon, West Java. Based on the results of the research, it is known that the content of heavy metals mercury (Hg) in sediments of 0.003 ± 0.006 ppm, green mussel P. viridis 0.027 ± 0.038 ppm, water 0.017 ± 0.029 ppm.Keywords: Green mussel, heavy metal mercury, rainy season, Cirebon water